The effect of Electronic Games on children during the Covid-19 pandemic: An Empirical Study for students at Abu Dhabi schools - Alketbi, Aisha Ali; Noufal, Zezit Mostafa (Al-Adab Journal, 2022)
The study aimed to identify the effect of electronic games on the psychological aspect of children during the Covid 19 pandemic, And to identify the effect of electronic games on the behavioral aspect of children under the Covid 19 pandemic, And to identify the effect of electronic games on the social aspect Children during the Covid 19 pandemic, And to identify the effect of electronic games on the academic aspect of children during the Covid-19 pandemic, And to identify the role of parents in limiting children’s practice of electronic games, And to identify the differences between males and females in the use of electronic games on children during the Covid 19 pandemic and to identify the means that help the child to play electronic games during the Covid 19 pandemic, the descriptive approach was used, on a random sample of children from the age of 6-17 years and the number of vocabulary was (312), and the researcher reached the following results: 1- Parents provide a lot of entertainment items that are not displayed on the screen (books, children’s magazines, games, puzzles, board games, etc.) in the rooms provided Use televisions, computers, and other devices with screens to encourage your child to do something unrelated to screens. 2- Parents keep TVs, iPads, and other screens out of your child’s bedroom. 3- Parents should not watch TV while performing their homework. 4- Parents treat TV time as a privilege that your child earns, not just something he deserves. Tell them that screen time only allowed when they finish with their home and school chores. Limit the time you spend watching TV. 5- As a parent, check out TV shows and reviews about the shows. Look for programs that the whole family can watch (e.g., age-appropriate, non-violent, and promoting family values). Choose programs that stimulate interest and learning related to hobbies and education (reading, science, etc.).